1948
DOI: 10.1021/ie50464a017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluctuating Storage Temperatures on Quality of Frozen Foods

Abstract: LUCTUATING temperatures due to many different condi-F tions may be encountered in the storage of frozen foods. Temporary breakdown of facilities or equipment, improper response of temperature controlling devices, excessive loads during freezing, lack of a separate compartment for freezing, and frequent opening of the cabinet (particularly a side-opening box) all may lead to a temporary rise in the temperature of the stored food.Statements in the literature (1, 3, 10) stress the point that temperature fluctuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1977
1977
2010
2010

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…Gortner et al (1948) stored pork loin roasts at constant and comparable conditions of fluctuating subfreezing temperatures and found that thiamin stability did not differ between these two conditions. Moleeratanond et al (1981) stored seven types of beef products for 1 year at three different temperature conditions: (1) constant _23°C, (2) fluctuating _23° to _21°C with 12 hr at each temperature, and (3) fluctuating -21 ° to _18°C with 12 hr at each temperature.…”
Section: Loss Of Nutrients During Freezingmentioning
confidence: 99%
See 2 more Smart Citations
“…Gortner et al (1948) stored pork loin roasts at constant and comparable conditions of fluctuating subfreezing temperatures and found that thiamin stability did not differ between these two conditions. Moleeratanond et al (1981) stored seven types of beef products for 1 year at three different temperature conditions: (1) constant _23°C, (2) fluctuating _23° to _21°C with 12 hr at each temperature, and (3) fluctuating -21 ° to _18°C with 12 hr at each temperature.…”
Section: Loss Of Nutrients During Freezingmentioning
confidence: 99%
“…With respect to frozen green peas (Boggs et at. 1960;Gortner et at. 1948), frozen cauliflower (Dietrich et at.…”
Section: A-asparagus Gb -Green Beans B-broccoli C-cauliflower Gp-greeunclassified
See 1 more Smart Citation
“…A b o u t 80% of the packages contained an appreciable amount of frost, and 14% contained an excessive amount of frost within the retail packages of frozen vegetables studied. The effect of temperature fluctuation upon the rate of in-package frost and cavity ice formation has been found by Gortner et al (1948) and Klose et al (1955). The conclusions of their studies were that frost formation increased with temperature, and for the -23.3"C to -122°C fluctuation frost formation was considerably greater than for the highest, -12.2"C, constant temperature.…”
Section: Schwimmer Integrated This Equation Term-by-term By Using Thementioning
confidence: 92%
“…Some authors consider temperature fl uctuations to have the same effect on the quality of the product as storage at an average constant temperature (Dawson 1971 ); others consider that fl uctuations may have an additive effect (Van Arsdel 1969 ; Bech -Jacobsen and B ø gh -S ø rensen 1984 ). There is evidence that exposure to temperatures warmer than − 18 ° C rather than temperature fl uctuations may be the major factor infl uencing quality deterioration (Gortner et al 1948 ). of meat.…”
Section: Packagingmentioning
confidence: 99%